Solutions and Ulam-Hyers stability of differential inclusions involving Suzuki type multivalued mappings on b-metric spaces - Abbas, Mujahid; Ali, Basit; Nazir, Talat; Dedović, Nebojša; Bin-Mohsin, Bandar; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: This paper presents coincidence and common fixed points of Suzuki type  multivalued operators on b-metric spaces.Methods: The limit shadowing property was discussed as well as the well- posedness and the Ulam-Hyers stability of the solution for the fixed point problem of such operators.Results: The upper bound of the Hausdorff distance between the fixed point sets is obtained. Some examples are presented to support the obtained results.Conclusion: The application of the obtained results establishes the existence of differential inclusion.
Keywords: b-metric space; multi-valued mapping; fixed point problems; Ulam-Hyers stability; initial value problem